Hubungan Religiusitas dengan Quarter Life Crisis Mahasiswa Semester Akhir - Dimas Agil Permadi; Pria Nurbian; Suyanti Suyanti (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
Ideally, final-year undergraduates are expected to demonstrate psychological maturity and a clear sense of future direction. However, the pressure of academic demands and social expectations often precipitates a "quarter-life crisis," triggering profound anxiety during this transitional phase. This study investigates the relationship between religiosity and the quarter life crisis among final-year students at Universitas Ibrahimy Situbondo. Employing a quantitative correlational design, the study involved 149 students selected via convenience sampling from a population of 237. Data were collected using the Religiosity Scale and the Quarter-Life Crisis Scale, then analyzed using simple linear regression with JASP version 0.19.1.0. Contrary to common assumptions in religious settings, the findings revealed that religiosity was not significantly associated with the quarter life crisis (p = .105 > .05). The effective contribution of religiosity in explaining the variance of the crisis was minimal (R2 = 0.018 or 1.8%), indicating that 98.2% of the phenomenon is driven by factors outside the scope of this study. These results suggest that religiosity is not a sole predictor capable of buffering against quarter life crisis. Consequently, further research should explore other potential mitigating variables, such as social support, self-efficacy, or career adaptability, particularly within Islamic boarding school-based university environments.